Gangliosides in the Brain: Physiology, Pathophysiology and Therapeutic Applications - Sipione, Simonetta; Monyror, John; Galleguillos, Danny; Steinberg, Noam; Kadam, Vaibhavi (Frontiers in Neuroscience, 2020)
Gangliosides are glycosphingolipids highly abundant in the nervous system, and carry most of the sialic acid residues in the brain. Gangliosides are enriched in cell membrane microdomains (“lipid rafts”) and play important roles in the modulation of membrane proteins and ion channels, in cell signaling and in the communication among cells. The importance of gangliosides in the brain is highlighted by the fact that loss of function mutations in ganglioside biosynthetic enzymes result in severe neurodegenerative disorders, often characterized by very early or childhood onset. In addition, changes in the ganglioside profile (i.e. in the relative abundance of specific gangliosides) were reported in healthy ageing and in common neurological conditions, including Huntington’s disease (HD), Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), stroke, multiple sclerosis and epilepsy. At least in HD, PD and in some forms of epilepsy, experimental evidence strongly suggests a potential role of gangliosides in disease pathogenesis and potential treatment. In this review, we will summarize ganglioside functions that are crucial to maintain brain health, we will review changes in ganglioside levels that occur in major neurological conditions and we will discuss their contribution to cellular dysfunctions and disease pathogenesis. Finally, we will review evidence of the beneficial roles exerted by gangliosides, GM1 in particular, in disease models and in clinical trials.